Drug delivery nanosystems in glioblastoma multiforme treatment: Current state of the art - Di Filippo, Leonardo Delello [UNESP] (2021)
Glioblastoma multiforme (GBM) is the most common primary malignant Central Nervous System cancer, responsible for about 4% of all deaths associated with neoplasia, characterized as one of the fatal human cancers. Tumor resection does not possess curative character, thereby radio and/or chemotherapy are often necessary for the treatment of GBM. However, drugs used in GBM chemotherapy present some limitations, such as side effects associated with non-specific drug biodistribution as well as limited bioavailability, which limits their clinical use. To attenuate the systemic toxicity and overcome the poor bioavailability, a very attractive approach is drug encapsulation in drug delivery nanosystems. The main focus of this review is to explore the actual cancer global problem, enunciate barriers to overcome in the pharmacological treatment of GBM, as well as the most updated drug delivery nanosystems for GBM treatment and how they influence biopharmaceutical properties of anti-GBM drugs. The discussion will approach lipid-based and polymeric nanosystems, as well as inorganic nanoparticles, regarding their technical aspects as well as biological effects in GBM treatment. Furthermore, the current state of the art, challenges to overcome and future perspectives in GBM treatment will be discussed.